2018
DOI: 10.1016/j.aap.2017.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Accident frequency and unrealistic optimism: Children’s assessment of risk

Abstract: Accidental injury is a major cause of mortality and morbidity among children, warranting research on their risk perceptions. Three hundred and seven children aged 10-11 years assessed the frequency, danger and personal risk likelihood of 8 accidents. Two social-cognitive biases were manifested. The frequency of rare accidents (e.g. drowning) was overestimated, and the frequency of common accidents (e.g. bike accidents) underestimated; and the majority of children showed unrealistic optimism tending to see them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Another factor that can affect study results is de-biasing effect which is the suppression of unrealistic optimism by having a negative experience [ 14 ]. Such changes in bias with regard to unrealistic optimism were reported for the effect of frequency of accidents on the attitude of children towards risk taking [ 15 ]. This adverse effect of negative experience on study results was recognised.…”
Section: Introductionmentioning
confidence: 81%
“…Another factor that can affect study results is de-biasing effect which is the suppression of unrealistic optimism by having a negative experience [ 14 ]. Such changes in bias with regard to unrealistic optimism were reported for the effect of frequency of accidents on the attitude of children towards risk taking [ 15 ]. This adverse effect of negative experience on study results was recognised.…”
Section: Introductionmentioning
confidence: 81%
“…This section was only completed by adults with DCD (i.e., not the parents). These participants were shown a series of pictures taken from Sissons Joshi et al (2017) and asked whether they felt the accident shown in the picture was more, the same amount or less likely to happen to them compared to their peers, if they provided an answer of more or less they were asked to provide a justification for their answer. The pictures depicted: an accident while cycling; an accident in the bath; an accident when pouring from a kettle; an accident on a trampoline; an accident while swimming; an accident in a thunderstorm; an accident with a dog and an accident when crossing the road.…”
Section: Methodsmentioning
confidence: 99%
“…Studies which have demonstrated unrealistic optimism in typical adults include, but are not limited to, estimating the risk of a heart attack ( Radcliffe and Klein, 2002 ), the risk of experiencing severe alcohol problems in the future ( Dillard et al, 2006 ), women’s estimated risk for breast cancer ( Waters et al, 2011 ), and smokers’ estimated risk of cancer ( Ayanian and Cleary, 1999 ). Unrealistic optimism has also been considered in children ( Sissons Joshi et al, 2017 ) with participants comparing the likelihood of common childhood accidents happening to them compared to their peers, children consistently stated that an accident was “less likely” to happen to them. Children cited reasons such as “heightened skill” or “lack of exposure” as reasons for why these accidents were less likely.…”
Section: Introductionmentioning
confidence: 99%
“…una explicación general a la relación entre el optimismo y la salud física está orientada a aspectos conductuales que intervienen en ésta, como mejor disposición al tratamiento, mejor manejo de los desafíos físicos, mayor sensación de autoeficacia y comportamientos más saludables que contribuyen a la mejoría del estado de salud física (Williams, Davis, hancock y Phipps, 2009). Contrario a lo antes expuesto, existe evidencia que propone que el optimismo puede generar prejuicios sociocognitivos que alteran la percepción de riesgo de los niños y niñas, generando una falsa sensación de seguridad que pudiera exponer la salud física y psicológica de éstos (Joshi, Maclean y Stevens, 2018;Metzger, Flanagin y Nekmat, 2015). Es en este sentido, que la psicología de la salud -espacio donde mayormente se han desarrollado estudios en este ámbito -debe poner su atención para desarrollar planes de apoyo o intervenciones más completas.…”
Section: Consecuencias Del Optimismo En La Infanciaunclassified